2004
DOI: 10.1111/j.0953-816x.2004.03334.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term synaptic morphometry changes after induction of long‐term potentiation and long‐term depression in the dentate gyrus of awake rats are not simply mirror phenomena

Abstract: Mechanisms of expression of long-term synaptic plasticity are believed to involve morphological changes of the activated synapses and remodelling of connectivity. Here, we investigated changes in synaptic and neuronal parameters in the dentate gyrus 24 h after induction of long-term potentiation (LTP) and long-term depression (LTD) in awake rats. In dentate granule cells, tetanization of the medial or lateral perforant paths induces LTP in specific synaptic bands along the dendrites in the middle and outer mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…All electrophysiological data were obtained in awake rats and experimental procedures were similar to those previously reported (Mezey et al, 2004). In short, after 3 days of habituation to the recording chamber (30 min each day) during which input/output curves and convergence and summation tests were carried out, a pre-HFS baseline was recorded by stimulating alternately the two pathways at 15 s intervals for 20 min using test intensities (mean 400 mA, 80-120 ms) to evoke MPP and LPP EPSP slopes of approximately half its maximum.…”
Section: Electrophysiology and Experimental Designmentioning
confidence: 89%
See 2 more Smart Citations
“…All electrophysiological data were obtained in awake rats and experimental procedures were similar to those previously reported (Mezey et al, 2004). In short, after 3 days of habituation to the recording chamber (30 min each day) during which input/output curves and convergence and summation tests were carried out, a pre-HFS baseline was recorded by stimulating alternately the two pathways at 15 s intervals for 20 min using test intensities (mean 400 mA, 80-120 ms) to evoke MPP and LPP EPSP slopes of approximately half its maximum.…”
Section: Electrophysiology and Experimental Designmentioning
confidence: 89%
“…1) and was blocked by the presence of the NMDA receptor antagonist CPP immediately (magnitude at 30 min 22.64 + 4.06% change; significant difference with LTP groups, F 1,11 ¼ 30.8, P , 0.001) and for 24 h (6.62 + 2.83% change, n ¼ 4). As described in our previous investigations (Doyere et al, 1997;Mezey et al, 2004), potentiation of the LPP (21.73 + 8.30% change at 2 h, n ¼ 5; 39.80 + 8.60% change at 24 h, n ¼ 4; data not shown) resulted immediately in heterosynaptic LTD of the MPP with a magnitude of 220.57 + 3.30% change (n ¼ 9) 30 min post-HFS, which was maintained at 2 h (214.30 + 3.69% change) and at 24 h (210.36 + 1.56% change at 24 h; Fig. 1).…”
Section: Electrophysiologymentioning
confidence: 89%
See 1 more Smart Citation
“…A quantitative 2-dimensional ultrastructural study in vivo looked at morphological correlates of heterosynaptic LTD in dentate gyrus of the awake rat (Mezey et al, 2004) and showed that LTD was not simply the converse of LTP. A non input-specific increase was found in unperforated axospinous synapses 24h after both LTP and LTD while the major effect of LTD alone was an input-specific increase in axodendritic synapse density.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Changes in synaptic and dendritic structure are believed to underlie synaptic plasticity in the hippocampus (Moser et al, 1994(Moser et al, , 1997Stewart et al, 2000;O'Malley et al, 2000;Nikonenko et al, 2002;Eyre et al, 2003;Muller and Nikonenko, 2003;Harris et al, 2003;Mezey et al, 2004;Popov et al, 2004). In rats stressed for 3-4 weeks, synaptic changes occur in CA3, including alterations in mossy fibre terminals (Magariños et al, 1997), a loss of synapses and a reduction in the surface area of postsynaptic densities (Sousa et al, 2000).…”
mentioning
confidence: 99%